Correction to: Mapping trust relationships in organ donation and transplantation: a conceptual model - Martínez-López, María Victoria; McLaughlin, Leah; Molina-Pérez, Alberto; Pabisiak, Krzysztof; Primc, Nadia; Randhawa, Gurch; Rodríguez-Arias, David; Suárez, Jorge; Wöhlke, Sabine; Delgado, Janet (BMC medical ethics, 2024)
The organ donation and transplantation (ODT) system heavily relies on the willingness of individuals to donate their organs. While it is widely believed that public trust plays a crucial role in shaping donation rates, the empirical support for this assumption remains limited. In order to bridge this knowledge gap, this article takes a foundational approach by elucidating the concept of trust within the context of ODT. By examining the stakeholders involved, identifying influential factors, and mapping the intricate trust relationships among trustors, trustees, and objects of trust, we aim to provide a comprehensive understanding of trust dynamics in ODT. We employ maps and graphs to illustrate the functioning of these trust relationships, enabling a visual representation of the complex interactions within the ODT system. Through this conceptual groundwork, we pave the way for future empirical research to investigate the link between trust and organ donation rates, informed by a clarified understanding of trust in ODT. This study can also provide valuable insights to inform interventions and policies aimed at enhancing organ donation rates.